Comparative Study Between Two Triple Therapy Regimens on Eradication of Helicobacter Pylori (HP) - Khanal, Sharad; Rao, B.S.; Sharma, Yubaraj; Khan, G.M.; Makaju, Ramesh (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Helicobacter pylori (HP) are a bacterium that infects the mucus lining of the human stomach. HP has emerged as one of the most common bacterial pathogens worldwide [1]. It is estimated that about half the world’s population is infected with HP [2]. Curing the infection has the best outcome and is clearly the most cost effective management strategy for HP infected patients with ulcer disease [3]. The goal of the therapy is to eradicate the infection. A comparison of two ‘triple therapy’ regimen to patient with Rapid Urease Test (RUT) and histologically proven HP infection and to evaluation of cost factor of two regimens is studies Regimen-I Omeprazole 20mg bid-Clarithromycin 500mg bid –Amoxicilin 1g bid; Regimen-II Omeprazole 20mg bid-Clarithromycin 500mg bid – Tinidazole-500mg bid. It was hypothesized that Omeprazole – Clarithromycin – Amoxycillin regimen is superior to Omeprazole – Clarithromycin – Tinidazole regimen for eradication of HP. The study was conducted from in Kathmandu University Teaching Hospital, (KUTH- DH), Dhulikhel, Nepal.Eradication rate of regimen-I and II was found 93.8% and 91.4% respectively, However there was no significant difference between regimen-I and II both are effective in eradication of HP. While analyzing cost difference between two regimens, it was found that regimen-II was cheaper (Rs.361.20 per course) than regimen-I and eradication rate was also satisfactory.